FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK TERHADAP TAX EVASION DI JAKARTA - YUDITHIA MARIA DATULALONG; YULIUS KURNIA SUSANTO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to achieve empirically evidence of the impact of the tax rates, technology and information, justice of the taxation system, subjective norm, discrimination, and understanding of taxation on the perception of individual taxpayer against tax evasion in DKI Jakarta. The Populationin this research is a individual taxpayers who have business activities and registered in DKI Jakarta. The study used a convenience sampling method in determining the sampl, with a total sampel of 65 respondents. States the result of tax rates, justice of taxation system, subjective norm has impact on the perception of taxpayer against tax evation. While technology and information, discrimination, and understanding of taxation has no impact on the perception of taxpayer against tax evation.